WEBSITE DEVELOPMENT AND PERFORMANCE IMPROVEMENT OF VILLAGE APPARATUS IN BETON VILLAGE - Isnaini Muhandhis; Rahma Alfiani Humairo; Supriyanto Supriyanto; M. Harist Murdani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Currently, Desa Beton Kec. Menganti , Gresik does not yet have a village website so that the existence and potential of the village are not well known to the public. The development of a village website is one way to introduce the village to the wider community. The professionalism of employees is very much needed for the success of a village organization. Therefore, there is a need for supervision to be able to maintain and improve the professionalism of employees, especially in Beton Village. Therefore, in this program, we aim to: (1) develop a village website as a medium of information and a forum for independent community service and (2) conduct job analysis as a source of information for improving the performance of the apparatus. The results of this service program are (1) Beton Village has a website that can be used to make it easier to get information in the form of the latest news related to tourist villages in the village so that it can attract many parties to visit Beton Village and also develop self-service, (2) the results of the evaluation of the job analysis are that every position in Beton Village has carried out its duties, obligations and functions by adhering to the Perka BKN applicable in Indonesia.